2020
DOI: 10.3390/polym12102208
|View full text |Cite
|
Sign up to set email alerts
|

Microbuckling Instability and the Second Yield during the Deformation of Semicrystalline Polyethylene

Abstract: Deformation instabilities, such as microbuckling or lamellar fragmentation due to slip localization, play a very important role in the deformation of semicrystalline polymers, although it still not well explored. Such instabilities often appear necessary to modify the deformation path and facilitate strain accommodation in an energy-minimizing manner. In this work, microbuckling instability was investigated using partially oriented, injection-molded (IM) samples of high-density polyethylene, deformed by a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 51 publications
(164 reference statements)
5
7
0
Order By: Relevance
“…Later, Sedighiamiri et al [ 48 ] proposed to associate the second yield with activation of the transverse slip systems rather than with the coarse chain slip. In the recent studies [ 20 , 21 , 22 ] we demonstrated that the second yield is actually related to the microbuckling instability occurring in the stacks of lamellae that were initially oriented along the direction of compression. The lamellae of such specific, longnitudinal orientation are not able to deform according to the usual crystallographic mechanisms because the corresponding resolved shear stresses are much lower than critical.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Later, Sedighiamiri et al [ 48 ] proposed to associate the second yield with activation of the transverse slip systems rather than with the coarse chain slip. In the recent studies [ 20 , 21 , 22 ] we demonstrated that the second yield is actually related to the microbuckling instability occurring in the stacks of lamellae that were initially oriented along the direction of compression. The lamellae of such specific, longnitudinal orientation are not able to deform according to the usual crystallographic mechanisms because the corresponding resolved shear stresses are much lower than critical.…”
Section: Resultsmentioning
confidence: 93%
“…Since microbuckling instability can effectively modify the deformation path, it often manifests macroscopically in the stress–strain curve as a characteristic low and broad hump, commonly referred to as the second yield. We reported in our previous papers [ 20 , 21 , 22 , 25 ] a hump related to the second yield in the stress-strain curves of several grades of polyethylene, observed around e ≈ 0.3–0.4 in the plane-strain compression. Concurrently, characteristic changes were observed in the 2D-SAXS and 2D-WAXS images, including the formation of a distinctive four-point SAXS pattern, which clearly indicated lamella kinking and development of a chevron-like morphology.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations